KORELASI KETERAMPILAN MENYIMAK BERITA DENGAN KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 2 BATUSANGKAR - Hidayatullah, Fitri; Arief, Ermawati; Rasyid, Yulianti (Universitas Negeri Padang, 2018)
ABSTRACT The article was written to describe thelistening skills of news text with the skills of writing news students class VIII SMP N 2 Batusangkar. The type of this study is quantitative research by using descriptive method. The research design used is correlational. Population in this study is students of grade VIII SMPN 2 Batusangkar registered in the academic year 2017/2018 amounted to 245 students. Sample were taken using proportional random sampling. Based on the result of this study, it can be concluded that correlation between listening skill with writing skill of news text student class VIII SMPN 2 Batusangkar with convidence 95% with degree of freedom n-1; t-count> t-table (5,55)> (1.68 ). Therefore, listening skills of news text has a correlation the skills of writing new text. Kata kunci: korelasi, keterampilan menyimak, keterampilan menulis, teks berita